Arqueologias do drama: uma arqueologia dramática - Rafael Guimaraes Tavares da Silva (2018)
The present work departs from an analysis of some influential theories about the origins of drama, since its first formulations in Antiquity mainly in the works of Plato and Aristotle, besides authors of the Hellenistic and the Imperial Roman periods up to its developments during the Middle Ages, the Renaissance and the Modern Age. Criticizing the interpretations offered by these theories to the corpus of poetic fragments and ancient testimonies relevant to the study of the subject, this investigation constitutes an original archaeology of drama, since it takes a critical position in relation to these traditional data, advancing a comprehensive and complex understanding of what underlies the gradual constitution of the dramatic genres in this period. Questioning the modern dicothomy between religion and politics, its proposal suggests that a historical phenomenon as such ought to be interpreted from different perspectives in order to be understood in all its complexity. It consists, therefore, in a work dedicated to a question of Poetics, i.e., to identify the origins of the dramatic genres in Athens from the gradual outset of the formal characteristics responsible to define them. To this end, a broad historical contextualization underlies a series of considerations relating to the origin of tragedy, comedy and satyric drama, mainly in connection with the gradual development of the dithyramb in the archaic period in Greece. Nevertheless, this investigation intends still to constitute an archaeology of the archaeologies of ancient drama, since putting in perspective extensively but not exhaustively different theories about the origins of the dramatic genres it seeks to sketch a hermeneutic panorama wide enough to offer a view of the ways in which these theories are embedded in their historical context, being responsible not only for conforming the comprehension of certain data related to the analyzed phenomenon, but also for defining which data ought to be held relevant to its comprehension. In this sense, departing from a metacritical exercice, the work develops a series of critical considerations about an aspect of the history of Poetics, culminating in notes of a metatheoric character, with implications for its own propositions of a new theory. For this, the ambivalence of the term arkhe present in the etymology of the word archaeology is fundamental, since, among other meanings, it refers to the notions of origin and power. In the light of what these analyses reveal about different archaeologies of drama, it is possible to defend that the most diverse (and even contradictory) theoretical proposals about the arkhe of drama are necessary to clarify the nuances of the complex emergence of dramatic genres in Antiquity, as well as its implications to a possible notion of Poetics.